Istorijos erdvės „užkariavimas" XXI a. Rusijoje: negatyvioji istorinė tapatybė? - Švedas, Aurimas (Lietuvos istorijos studijos, 2009)
The radical social and political changes experienced by the societies of the post-Soviet space determine the transformations in their sociocultural mentality and create new forms of relation with the past. The construction of a new historical identity, which now proceeds in contemporary Russia, can be considered as a typical process for the post-Soviet country, the particularity of which is created by several factors: traumatic experience and the particularities of sociopolitical life in a country that suffers transformation. The Russian State, which was built after the fall of the Soviet Union, had no clear ideology and value system for more than fifteen years. During this period, the elite of the state formed a utilitarian view towards various ideological systems, which could explain the development of reality through the concepts of political sciences and new models of historical narrative. In recent years all these components of sociopolitical identity have been used by the politicians of the Kremlin, the political scientists, and public relations’ specialists as an instrument for the production of a peculiar formation – the "state patriotism." The intellectual foundations of the "state patriotism" in the sphere of political science are such terms as "energetic superpower" and "sovereign democracy," which were used simultaneously in order to present Russia on the international stage and to provide the state regime – the vertical of power – with meaningfulness in the eyes of the inhabitants of the state. Eventually, it became obvious that such artificial and inadequate terms as "energetic superpower" and "sovereign democracy" cannot fully satisfy the needs of the ruling elite. The failure of political science manipulations to build a new social identity in Russia was partly compensated by the rise of the importance of historical narrative. Historical narrative in contemporary Russian society plays a role not only of compensatory but also of a consolidating mechanism. The historical narrative which is powerfully established and dominates in Russian society is selective, monological, and expansive; it allows one to call it "negative historical identity." Despite the peculiarities of this historical narrative on the Russian past, present, and future, its creators managed to ensure major public support for the narrative, which became a very important part of social mentality in contemporary Russia.